Etorphine-Azaperone Immobilisation for Translocation of Free-Ranging Masai Giraffes (Giraffa Camelopardalis Tippelskirchi): A Pilot Study - Francesca Vitali; Edward K. Kariuki; Domnic Mijele; Titus Kaitho; Massimo Faustini; Richard Preziosi; Francis Gakuya; Giuliano Ravasio (Animals, 2020)
Etorphine-azaperone immobilisation was evaluated for translocation of Masai giraffes. Nine giraffes were darted with 0.012 ± 0.001 mg/kg etorphine and 0.07 ± 0.01 mg/kg azaperone. Once ataxic, giraffes were roped for recumbency and restrained manually. Naltrexone (3 mg/mg etorphine) was immediately given intravenously to reverse etorphine-related side effects. Protocol evaluation included physiological monitoring, blood-gas analyses, anaesthetic times, and quality scores (1 = excellent, 4 = poor). Sedation onset and recumbency were achieved in 2.6 ± 0.8 and 5.6 ± 1.4 min. Cardio-respiratory function (HR = 70 ± 16, RR = 32 ± 8, MAP = 132 ± 16) and temperature (37.8 ± 0.5) were stable. Arterial gas analysis showed hypoxaemia in some individuals (PaO2 = 67 ± 8 mmHg) and metabolic acidosis (pH = 7.23 ± 0.05, PaCO2 = 34 ± 4 mmHg, HCO3− = 12.9 ± 1.2 mmol/l). Minor startle response occurred, while higher induction-induced excitement correlated to longer inductions, worse restraint, and decreased HCO3−. After 19 ± 3.5 min of restraint, giraffes were allowed to stand and were loaded onto a chariot. Immobilisations were good and scored 2 (1−3). Inductions and recoveries were smooth and scored 1 (1−2). Translocations were uneventful and no complications occurred in 14-days boma follow-up.